Transculturación y trans-identidades en la literatura contemporánea mexicana - Flores Badillo, Herlinda (Bridging languages and scholarship., 2022)
"Mexican history and culture have been transculturated since the pre-Hispanic era. The mixture that developed from the Spaniards arrival promoted the increase of transculturation and the development of new identities. Examples that can easily be spotted in Mexican contemporary literature, showing that due to this phenomena, Mexican literature is heterogeneous and diverse, not only in its canonic literature, but in that from the other Mexicos, or 'deep Mexico'. Transculturation and trans-identities in contemporary Mexican Literature explores identities in the works of Pablo Soler Frost, Álvaro Enrigue or Fernanda Melchor, to only cite a few. A book that will open a dialogue among researchers, academics and students whose area of study is related to the intersection of culture, identities, spaces, literature and writers. An ambitious collection of essays, of great interest regarding Mexican culture, but also 'border culture', migration, transcultural issues and identity politics."--